Geometric-Phase Waveplates for Free-Form Dark Hollow Beams - Piccirillo, Bruno; Piedipalumbo, Ester; Santamato, Enrico (Frontiers in Physics, 2020)
We demonstrate the possibility of creating optical beams with phase singularities engraved into exotic intensity landscapes imitating the shapes of a large variety of diverse plane curves. To achieve this aim, we have developed a method for directly encoding the geometric properties of a selected curve into a single azimuthal phase factor without passing through indirect encryption methods involving lengthy numerical procedures. The outcome is utilized to mold the optic axis distribution of a liquid-crystal-based inhomogeneous waveplate. The latter is finally used to sculpt the wavefront of an input optical gaussian beam via the Pancharatnam-Berry phase.